Polyimide microsphere coating modified battery diaphragm and lithium ion battery
By coating polyimide microspheres with the functions of adsorbing metal ions and exchanging lithium ions on the lithium-ion battery separator, the problem that existing lithium-ion battery separators cannot effectively adsorb metal ions is solved, and the cycling performance of the battery is significantly improved and Safety performance and improve the exchange and transmission performance of lithium ions.
Patent Information
- Application Number
- CN202411342870.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-02-07
AI Technical Summary
The existing lithium-ion battery separators cannot effectively adsorb metal ions dissolved inside the battery, causing metal ions to be deposited at the negative electrode, destroying the SEI film, and reducing the battery cycle performance and safety performance.
The modified battery separator is coated with polyimide microspheres, and polyimide microspheres with the functions of adsorbing metal ions and exchanging lithium ions are formed to form a coating to adsorb metal ions and promote lithium ions. exchange and transmission.
Effectively adsorbs metal ions dissolved inside the battery, reduce the deposition of metal ions at the negative electrode, improve the battery circulation and safety performance, and improve the exchange and transmission performance of lithium ions, and improve the charging and discharging efficiency of the battery.
Smart Images

Figure BDA0005060198450000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery separators, and in particular to a battery separator modified by coating with polyimide microspheres and a lithium ion battery. Background Art
[0002] Lithium-ion batteries have high energy density and cycle life, and are one of the preferred batteries for power devices and high-capacity electronic products. However, after cycling at room temperature and high temperature, the metal ions dissolved from the positive electrode of the lithium-ion battery will enter the electrolyte and diffuse through the lithium battery separator to the negative electrode of the lithium battery, and deposit on the surface of the graphite negative electrode. The metal deposits hinder the deintercalation of lithium ions in the graphite, thereby causing the reversible cycle capacity of the graphite electrode to decay.
[0003] The lithium-ion battery separator is located between the positive and negative electrodes of the lithium-ion battery. It is an electronic insulator that allows ions to migrate freely to achieve reversible "embedding" or "de-embedding" reactions. Therefore, from the perspective of separator design, fully adsorbing the metal ions dissolved inside the lithium-ion battery becomes an effective means to improve the battery's cycle performance and safety performance. At present, commercial lithium-ion batteries are still mainly based on polyolefin separators or ceramic separators, which cannot effectively adsorb metal ions. Summary of the invention
[0004] Based on the technical problems existing in the background technology, the present invention proposes a battery separator and a lithium-ion battery coated with polyimide microspheres. Polyimide microspheres with the function of adsorbing metal ions and exchanging lithium ions are used to form a base film coating, which can not only effectively adsorb the metal ions dissolved from the battery, reduce the deposition of metal ions at the negative electrode to damage the SEI film, and improve the battery cycle performance and safety performance, but also help to improve the lithium ion exchange and transmission performance of the separator, further improving the charge and discharge efficiency of the battery.
[0005] The present invention provides a polyimide microsphere-coated modified battery separator, comprising a base film and a coating formed by coating the surface of the base film;
[0006] The coating layer comprises polyimide microspheres having the functions of absorbing metal ions and exchanging lithium ions.
[0007] In the present invention, the battery separator includes a coating formed by coating on the surface of the base film, and the coating includes polyimide microspheres with the function of adsorbing metal ions and exchanging lithium ions. On the one hand, the polyimide microspheres can fully adsorb the metal ions dissolved from the lithium ion battery, avoiding the migration of metal impurity ions to the negative electrode during the charge and discharge process, which is beneficial to improving the cycle stability of the battery, reducing the self-discharge behavior of the battery cell caused by impurity elements, and reducing the increase in the internal resistance of the battery cell caused by the adsorption of impurity elements on the surface of the negative electrode material; on the other hand, the polyimide microspheres can form lithium salts, thereby improving the ion conductivity and inducing high-speed directional transmission of lithium ions along the battery separator, further improving the electrochemical performance of the battery.
[0008] Preferably, the polyimide microspheres are obtained by polycondensing diamine monomers and dianhydride monomers, electrostatically spraying, and then thermal imidization;
[0009] The diamine monomer includes a bulky diamine monomer and a sulfonic acid group-containing diamine monomer, and the dianhydride monomer includes pyromellitic dianhydride.
[0010] Preferably, the bulky diamine monomer is at least one of 2,4,6-trimethyl-m-phenylenediamine, 5-trifluoromethyl-1,3-phenylenediamine, 2,2'-bis(trifluoromethoxy)-biphenylenediamine, 9,9-bis(4-aminophenyl)fluorene or 4,4'-diaminooctafluorobiphenyl;
[0011] The sulfonic acid group-containing diamine monomer is at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 4,4'-diaminodiphenyl ether-2,2'-disulfonic acid, 4,4'-diaminobenzophenone-2,2'-disulfonic acid, 4,4'-diamino-2,2'-biphenyl disulfonic acid or 4,4'-diaminostilbene-2,2'-disulfonic acid;
[0012] Preferably, the molar ratio of the bulky diamine monomer to the sulfonic acid group-containing diamine monomer is 1-3:1.
[0013] Preferably, the dianhydride monomer further comprises at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride or 4,4'-oxydiphthalic anhydride.
[0014] In the present invention, a dianhydride monomer with a rigid structure and a bulky diamine monomer are introduced into the molecular chain of the polyimide microsphere, which, on the one hand, increases the rigidity of the molecular chain skeleton and reduces the activity of the molecular chain segments; on the other hand, increases the distance between the molecular chains, destroys the orderly stacking degree of the polyimide branch segments, weakens the interaction between the molecular chains, increases the free volume and specific surface area of the polyimide, and obtains a rich self-polymerized microporous structure; at the same time, a sulfonic acid group-containing diamine monomer is also introduced into the molecular chain of the polyimide microsphere, which can combine with lithium ions to form lithium sulfonate, which is beneficial to the exchange and transmission of lithium ions.
[0015] Preferably, the particle size of the polyimide microspheres is 0.02-10 μm.
[0016] Preferably, the coating further comprises inorganic particles;
[0017] Preferably, the inorganic particles are at least one of aluminum oxide, boehmite, magnesium oxide, zirconium oxide, titanium oxide, barium titanate, zinc oxide, calcium oxide, silicon dioxide or silicon carbide;
[0018] Preferably, the mass ratio of the inorganic particles to the polyimide microspheres is 100:1-20.
[0019] Preferably, the coating further comprises a binder;
[0020] Preferably, the binder is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, butadiene-acrylonitrile polymer or polyvinyl pyrrolidone;
[0021] Preferably, the mass ratio of the binder to the polyimide microspheres is 10:1-5.
[0022] Preferably, the coating is obtained by coating a slurry containing polyimide microspheres on at least one surface of the base film and curing the slurry.
[0023] Preferably, the coating method is at least one of gravure coating, extrusion coating, transfer coating, dip coating or wire rod coating.
[0024] The present invention also provides a lithium ion battery, which comprises the battery separator.
[0025] The invention provides a battery separator and a lithium ion battery modified by coating with polyimide microspheres. The coating formed by coating on the surface of a base film contains polyimide microspheres with the functions of adsorbing metal ions and exchanging lithium ions. On the one hand, the polyimide microspheres can adsorb metal ions, especially transition metal ions precipitated from a positive electrode, thereby preventing transition metal ions from forming transition metal precipitates on the surface of a negative electrode, thereby improving the cycle stability and safety performance of the battery. On the other hand, the polyimide microspheres can coordinate well with lithium ions, and on the premise of promoting lithium ion transmission, they can well prevent transition metal ions in an electrolyte from being transmitted to the negative electrode, thereby greatly alleviating the phenomenon of lithium precipitation at the negative electrode of the battery. DETAILED DESCRIPTION
[0026] The technical solutions of the present invention are described in detail below through specific embodiments. However, it should be clearly stated that these embodiments are for illustration only and are not to be construed as limiting the scope of the present invention.
[0027] Example 1
[0028] A polyimide microsphere-coated modified battery separator is prepared by the following method:
[0029] (1) adding pyromellitic anhydride, 2,4,6-trimethyl-m-phenylenediamine and 2,5-diaminobenzenesulfonic acid in a molar ratio of 1.02:0.7:0.3 to N,N-dimethylformamide and uniformly dispersing them, reacting under nitrogen protection to obtain a polyamic acid solution with a solid content of 10 wt%, electrostatically spraying in an electric field with an electric field strength of 1 kV / cm to obtain polyamic acid microspheres, heating the temperature from room temperature to 280° C. at a heating rate of 5° C. / min, and then thermal imidization treatment for 1 h to obtain polyimide microspheres;
[0030] (2) adding polyimide microspheres (average particle size of 0.6 μm), alumina powder (average particle size of 0.2 μm) and sodium carboxymethyl cellulose in a mass ratio of 10:100:1.5 to a mixed solvent of water and ethanol (volume ratio of 95:5), and uniformly dispersing them by high-speed stirring at a speed of 1000 r / min to obtain a slurry (solid content of 25 wt%);
[0031] (3) The slurry is coated on one surface of a polyethylene single-layer separator (thickness of 12 μm, porosity of 45%) by gravure coating to form a coating with a thickness of 4 μm. After drying at 60° C., the battery separator is obtained.
[0032] Example 2
[0033] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 5-trifluoromethyl-1,3-phenylenediamine and 4,4'-diaminodiphenyl ether-2,2'-disulfonic acid are added to N,N-dimethylformamide in a molar ratio of 1.02:0.6:0.4 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0034] Example 3
[0035] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 2,2'-bis(trifluoromethoxy)-biphenylenediamine and 4,4'-diaminobenzophenone-2,2'-disulfonic acid are added to N,N-dimethylformamide in a molar ratio of 1.02:0.5:0.5 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0036] Example 4
[0037] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride and 9,9-bis(4-aminophenyl)fluorene and 4,4'-diamino-2,2'-biphenyl disulfonic acid are added to N,N-dimethylformamide in a molar ratio of 1.02:0.6:0.4 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0038] Example 5
[0039] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 4,4'-diaminooctafluorobiphenyl and 2,4-diaminobenzenesulfonic acid are added to N,N-dimethylformamide in a molar ratio of 1.02:0.6:0.4 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0040] Example 6
[0041] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 3,3',4,4'-biphenyltetracarboxylic anhydride, 2,4,6-trimethyl-m-phenylenediamine and 2,5-diaminobenzenesulfonic acid are added to N,N-dimethylformamide in a molar ratio of 0.62:0.4:0.7:0.3 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0042] Example 7
[0043] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride, 2,4,6-trimethylm-phenylenediamine and 2,5-diaminobenzenesulfonic acid are added to N,N-dimethylformamide in a molar ratio of 0.52:0.5:0.7:0.3 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0044] Example 8
[0045] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride, 4,4'-oxydiphthalic anhydride, 2,4,6-trimethylm-phenylenediamine and 2,5-diaminobenzenesulfonic acid are added to N,N-dimethylformamide in a molar ratio of 0.62:0.4:0.7:0.3 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0046] Comparative Example 1
[0047] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride and p-phenylenediamine are added to N,N-dimethylformamide at a molar ratio of 1.02:1 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then thermally imidized for 1h to obtain polyimide microspheres.
[0048] Comparative Example 2
[0049] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), pyromellitic anhydride and 2,4,6-trimethyl-m-phenylenediamine are added to N,N-dimethylformamide at a molar ratio of 1.02:1 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then thermally imidized for 1h to obtain polyimide microspheres.
[0050] Comparative Example 3
[0051] A polyimide microsphere-coated modified battery separator, the preparation method of which is the same as that of Example 1, except that in step (1), 3,3',4,4'-biphenyltetracarboxylic acid anhydride, 2,4,6-trimethyl-m-phenylenediamine and 2,5-diaminobenzenesulfonic acid are added to N,N-dimethylformamide in a molar ratio of 1.02:0.7:0.3 and dispersed evenly, reacted under nitrogen protection to obtain a polyamic acid solution with a solid content of 10wt%, electrostatically sprayed in an electric field with an electric field strength of 1kV / cm to obtain polyamic acid microspheres, and heated from room temperature to 280°C at a heating rate of 5°C / min, and then subjected to thermal imidization treatment for 1h to obtain polyimide microspheres.
[0052] Performance Testing:
[0053] The battery separators obtained in the above examples and comparative examples were subjected to the following performance tests, respectively, and the results are shown in Table 1 below.
[0054] Ionic conductivity: After the obtained battery separator is cut into discs, it is placed between two stainless steel electrodes and absorbs enough electrolyte (lithium hexafluorophosphate electrolyte, concentration is 1 mol / L, the molar ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 1:1:1). The ionic conductivity is calculated as L / A·R (L is the thickness of the battery separator / cm, A is the contact area between the stainless steel plate and the separator / cm 2 , R is the bulk resistance of the electrolyte / mS);
[0055] Cycle performance: The obtained battery separator is assembled into a lithium-ion battery in a conventional manner with a positive electrode sheet (lithium cobalt oxide, conductive agent acetylene black, and polyvinylidene fluoride are mixed uniformly in an N-methylpyrrolidone solvent in a mass ratio of 97:1:2 to form a positive electrode slurry, which is coated on an aluminum foil and dried, and then cold pressed and stripped to form a positive electrode sheet), a negative electrode sheet (graphite, conductive carbon black SuperP, and styrene-butadiene rubber are mixed uniformly in a mass ratio of 97:1:2 in deionized water to form a negative electrode slurry, which is coated on a copper foil and dried, and then cold pressed and stripped to form a negative electrode sheet) and a 1 mol / L lithium hexafluorophosphate electrolyte (concentration is 1 mol / L, and the molar ratio of ethylene carbonate EC, dimethyl carbonate DMC and ethyl methyl carbonate EMC is 1:1:1), and then the battery performance is tested. Specifically, the charge and discharge cycle is carried out 500 times at a rate of 1C at room temperature or 50°C, and the capacity retention rate of 500 times is recorded.
[0056] Table 1 Performance test results of the battery separators described in Examples and Comparative Examples
[0057]
[0058] As shown in the results in Table 1, compared with the comparative example, the battery separator in the embodiment has better ionic conductivity and better battery capacity retention rate at both room temperature and high temperature, thereby improving the cycle performance and safety performance of the battery.
[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A battery separator modified by coating with polyimide microspheres, characterized in that: It includes a base film and a coating formed by coating on the surface of the base film; The coating layer comprises polyimide microspheres having the functions of absorbing metal ions and exchanging lithium ions.
2. The battery separator modified by coating with polyimide microspheres according to claim 1, characterized in that: The polyimide microspheres are obtained by polycondensing diamine monomers and dianhydride monomers, electrostatically spraying, and then thermal imidization; The diamine monomer includes a bulky diamine monomer and a sulfonic acid group-containing diamine monomer, and the dianhydride monomer includes pyromellitic dianhydride.
3. The battery separator modified by coating with polyimide microspheres according to claim 2, characterized in that: The bulky diamine monomer is at least one of 2,4,6-trimethyl-m-phenylenediamine, 5-trifluoromethyl-1,3-phenylenediamine, 2,2'-bis(trifluoromethoxy)-biphenylenediamine, 9,9-bis(4-aminophenyl)fluorene or 4,4'-diaminooctafluorobiphenyl; The sulfonic acid group-containing diamine monomer is at least one of 2,5-diaminobenzenesulfonic acid, 2,4-diaminobenzenesulfonic acid, 4,4'-diaminodiphenyl ether-2,2'-disulfonic acid, 4,4'-diaminobenzophenone-2,2'-disulfonic acid, 4,4'-diamino-2,2'-biphenyl disulfonic acid or 4,4'-diaminostilbene-2,2'-disulfonic acid; Preferably, the molar ratio of the bulky diamine monomer to the sulfonic acid group-containing diamine monomer is 1-3:
1.
4. The battery separator modified by coating with polyimide microspheres according to claim 2 or 3, characterized in that: The dianhydride monomer further comprises at least one of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 4,4'-(hexafluoroisopropylene) diphthalic anhydride or 4,4'-oxydiphthalic anhydride.
5. The battery separator modified by coating with polyimide microspheres according to any one of claims 1 to 4, characterized in that: The particle size of the polyimide microspheres is 0.02-10 μm.
6. The battery separator modified by coating with polyimide microspheres according to any one of claims 1 to 5, characterized in that: The coating also includes inorganic particles; Preferably, the inorganic particles are at least one of aluminum oxide, boehmite, magnesium oxide, zirconium oxide, titanium oxide, barium titanate, zinc oxide, calcium oxide, silicon dioxide or silicon carbide; Preferably, the mass ratio of the inorganic particles to the polyimide microspheres is 100:1-20.
7. The battery separator modified by coating with polyimide microspheres according to any one of claims 1 to 6, characterized in that: The coating also includes a binder; Preferably, the binder is at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyacrylic acid, polymethacrylic acid, polyacrylate, polymethyl methacrylate, polyacrylonitrile, sodium carboxymethyl cellulose, butadiene-acrylonitrile polymer or polyvinyl pyrrolidone; Preferably, the mass ratio of the binder to the polyimide microspheres is 10:1-5.
8. The battery separator modified by coating with polyimide microspheres according to any one of claims 1 to 7, characterized in that: The coating is obtained by coating a slurry containing polyimide microspheres on at least one surface of the base film and curing the slurry.
9. The battery separator modified by coating with polyimide microspheres according to any one of claims 1 to 8, characterized in that: The coating method is at least one of gravure coating, extrusion coating, transfer coating, dip coating or wire rod coating.
10. A lithium ion battery, characterized in that: It comprises the battery separator according to any one of claims 1 to 9.
Citation Information
Cited By
Polyimide microsphere modified composite diaphragm as well as preparation method and application thereof
CN120199972A
High-permeability high-temperature-resistant lithium battery coating diaphragm and preparation method thereof
CN120511434A
Modified ceramic powder, ceramic composite diaphragm and lithium ion battery
CN120810173A